Quality of Life in Prodromal HD: Qualitative Analyses of Discourse from Participants and Companions - Rebecca E. Ready; Justin J. F. O'Rourke; Jane S. Paulsen (Neurology Research International)
Persons who are at risk for Huntington's Disease (HD) can be tested for the HD gene expansion before symptom onset. People with the gene expansion, but no clinical diagnosis, are in the prodromal phase of HD. This study explored quality of life (QOL) in prodromal HD. Interviews about QOL, conducted with 9 prodromal HD participants and 6 companions, were transcribed. Discourse was coded for emotional valence, content (e.g., coping, spirituality, interpersonal relationships, HD in others, and employment), and time frame (e.g., current, past, and future). Respondents were more positive than negative about the present, which was their major focus. The most common statements were about positive attitudes. Positive statements were made about spirituality, and negative statements were made about HD in other people. Relationships, employment, and coping with HD reflected both positivity and negativity. Participants and companions spoke of the future with different concerns. Applicability of findings to the clinical management of HD are discussed.